Politeness Strategies in Deddy Corbuzier's Close The Door Podcast - Pratama, Mahendra Surya; Ardi, Havid (Universitas Negeri Padang, 2024)
This research aims to discover the differences between Deddy Corbuzier's politeness strategies towards male and female guests in Close The Door Podcast. Qualitative method is used for this research. The data were gathered from two videos of Close The Door Podcast featuring two guests from roughly the same background but different genders. Politeness theory proposed by Brown and Levinson were used to analyze the data. The results shows that that Deddy Corbuzier used all four types of politeness strategies towards both male and female guests. The findings also discovered Corbuzier used more negative politeness towards female guest than the male guest, while he used other types of politeness strategies, especially positive politeness, more towards the male guest. Additionally, there are several strategies Corbuzier exclusively used towards the female guest, and vice-versa. As such, it can be concluded that in communication, Corbuzier uses different politeness strategies when addressing male and female hearer.